Break the Silence: Pakistani Women Facing Violence - Dr. Rukhsana Iftikhar; Dr.Maqbool Ahmad Awan (Journal of Political Studies, 2019)
Women have always been treated as second grade citizen in Pakistan. Pakistan is considered the 3rd unsafe country for women to live. Pakistani women are facing problems in their private and public life. Violence is the most thriving issue for the women in Pakistan. The main reason of the wide spread violence is poverty and ignorance. Social structure is not supporting woman although gender ratio of population is more than half. This paper is an attempt to explore the causes and types of violence in Pakistan. It also deals with the effects of violence in society. State has introduced a number of legislations but the common woman in Pakistan is conscious about her rights. The state of Pakistan is not progressed without the help of other gender. State and women both have to take the task to eradicate the issue of violence.